Future thinking and its relationship to meta-emotion among university students (Journal of the College of Basic Education, 2022)
Abstract The paper aims sat finding out the following: Investigating future thinking in university students.Meta-emotional aspects in university students.The relationship between the future thinking and Meta-emotional a sample from university students.The statistically significant differences in the correlative relationship between future thinking and meta-emotional in terms of gender, specialization, and class. To achieve these objectives, a sample of students from the University of Qadisiyah (400) students and students were selected for a total of 10 scientific disciplines and humanity for the academic year 2017-2018 was chosen in a stratified and proportional manner, and a measure of future thinking was built upon Similar studies and theoretical literature consists of (28) a paragraph divided into three areas, and the properties of its cycoometric have been extracted from the sincerity and steadiness, the researchers adopted the Gottman, 2014, for the passion, and after adapting it to the research community and subjecting it to statistical analysis and the extraction of properties The Cyclometric has a final form of 40-paragraph and after the two tools have been applied to the search sample, it turns out that the search sample has a future thinking., the search sample enjoyed the attributes of the emotion but was not statistically significant, while statistical differences showed at 0.05 in the relational relationship. Between future thinking and emotion depending on the gender, specialization and class of university students, the research came out with a number of recommendations and suggestions.